New imaging modalities in peripheral interventions. (9th March 2015) - Micari, Antonio; Sbarzaglia, Paolo; Meeks, M.D.M.E.; Liso, Armando; Riina, Marco; Lunetto, Maria Letizia; Roscitano, Giuseppe; Vadalà, Giuseppe
Abstract: The aim of this article is to evaluate the feasibility and results of our peripheral revascularization where we used non-conventional intra-procedural imaging techniques. Between January 2014 and September 2014, 45 patients were imaged with CO2 angiography and/or optical coherence tomography (OCT) or 2D perfusion imaging. The scope was to minimize the use of contrast and obtain additional information to improve the outcome. CO2 angiography was used in all patients with impaired renal function. Two-dimensional perfusion was used in all patients with critical limb ischaemia before and after revascularization to quantify angiosome blood supply improvement at wound level. Optical coherence tomography was performed in superficial femoral arteries and popliteal arteries to disclose vessel microstructure and characterize plaque structure. In all patients, the invasive imaging was feasible and safe. In those patients studied with CO2, the creatinine serum level after procedure increased by 0.11 ± 0.05. None of the patients received dialysis. The procedural success rate was 100% and was no different from the historical sample of the cath lab. Procedural time was not significantly affected by this supplemental technique. The 2D perfusion showed an incremental blood supply at wound level and OCT provided encouraging details regarding dissections and their clinical relevance. Our early experience with supplementary imaging techniques showed safety and feasibility. The peripheral angioplasty success rate was not different from the historical sample and the reduction of the contrast media dose resulted in an encouraging outcome in terms of renal protection. Two-dimensional perfusion added objective information regarding blood supply improvement and guided re-perfusion strategy.